2018
DOI: 10.3390/tropicalmed3020064
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric Strongyloidiasis in Central Australia

Abstract: Few published studies are available describing the prevalence of paediatric strongyloidiasis in endemic areas within Australia. This literature review and exploratory clinical audit presents the first seroprevalence data for paediatric patients in Central Australia. A total of 16.1% (30/186) of paediatric inpatients tested for Strongyloides stercoralis in 2016 were seropositive (95% CI: 11.5% to 22.1%). Eosinophilia of unknown aetiology was the most common indication for testing (91.9%). Seropositive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
3
3
0
Order By: Relevance
“…Confounders such as the precarious socioeconomic conditions in which participants lived, which increased risk of exposure to Strongyloides and to malnutrition, might be the more important cause of anaemia and complicate the interpretation of these studies [ 47 ]. In the present study, and in a previous study of childhood strongyloidiasis in central Australia [ 48 ], all participants lived in similarly disadvantaged circumstances with ready access to health clinics and there was no association between anaemia and Strongyloides seropositivity.…”
Section: Discussionsupporting
confidence: 56%
“…Confounders such as the precarious socioeconomic conditions in which participants lived, which increased risk of exposure to Strongyloides and to malnutrition, might be the more important cause of anaemia and complicate the interpretation of these studies [ 47 ]. In the present study, and in a previous study of childhood strongyloidiasis in central Australia [ 48 ], all participants lived in similarly disadvantaged circumstances with ready access to health clinics and there was no association between anaemia and Strongyloides seropositivity.…”
Section: Discussionsupporting
confidence: 56%
“…seroprevalence was 27% (5-42%) [5]. This is comparable with a study (based on literature and exploratory clinical audit) in central Australia that found 16% (30/186) of paediatric inpatients that were tested for S. stercoralis were seropositive [11]. Shield et al [12] reported positive cases across all states and territories in Australia, with the highest (17-40% of those tested) in regions across where many First Nations people live in remote communities.…”
Section: Introduction (A) Strongyloidiasissupporting
confidence: 62%
“…Some of the pathogens detected in the evidence base are of public health importance such as antimicrobial resistant bacteria, with community associated methicillin resistant Staphylococcus aureus disproportionately affecting Aboriginal people [27,40]. The prevalence of Strongyloides stercoralis is also disproportionately high in Aboriginal communities in Australia [24,30]. Strongyloides is a neglected tropical disease, which refers to diseases prevalent in tropical areas that mainly affect low-resourced communities [51].…”
Section: Discussionmentioning
confidence: 99%